Three-Dimensional Magnetic Resonance Imaging for Guiding Tibial and Femoral Tunnel Position in Anterior Cruciate Ligament Reconstruction: A Cadaveric Study. Issue 3 (27th March 2020) - Marwan, Yousef; Böttcher, Jens; Laverdière, Carl; Jaffer, Rehana; Burman, Mark; Boily, Mathieu; Martineau, Paul A.
Background: Femoral and tibial tunnel malposition for anterior cruciate ligament (ACL) reconstruction (ACLR) is correlated with higher failure rate. Regardless of the surgical technique used to create ACL tunnels, significant mismatches between the native and reconstructed footprints exist. Purpose: To compare the position of tunnels created by a standard technique with the ones created based on preoperative 3-dimensional magnetic resonance imaging (3D MRI) measurements of the ACL anatomic footprint. Study Design: Controlled laboratory study. Methods: Using 3D MRI, the native ACL footprints were identified. Tunnels were created on 16 knees (8 cadavers) arthroscopically. On one knee of a matched pair, the tunnels were created based on 3D MRI measurements that were provided to the surgeon (roadmapped technique), while on the contralateral knee, the tunnels were created based on a standard anatomic ACLR technique. The technique was randomly assigned per set of knees. Postoperatively, the positions of the tunnels were measured using 3D MRI. Results: On the tibial side, the median distance between the center of the native and reconstructed ACL footprints in relation to the root of the anterior horn of the lateral meniscus medially was 1.7 ± 2.2 mm and 1.9 ± 2.8 mm for the standard and roadmapped techniques, respectively ( P = .442), while the median anteroposterior distance was 3.4 ± 2.4 mm and 2.5 ± 2.5 mm for the standard and roadmapped techniques, respectively ( P = .161). On the femoral side, the median distance in relation to the apex of the deep cartilage (ADC) distally was 0.9 ± 2.8 mm and 1.3 ± 2.1 mm for the standard and roadmapped techniques, respectively ( P = .195), while the median distance anteriorly from the ADC was 1.2 ± 1.3 mm and 4.6 ± 4.5 mm for the standard and roadmapped techniques, respectively ( P = .007). Conclusion: Providing precise radiological measurements of the ACL footprints does not improve the surgeon's ability to position the tunnels. Future studies should continue to attempt to provide tools to improve the tunnel position in ACLR. Clinical Relevance: This cadaveric study indicates that despite the use of 3D MRI in understanding the ACL anatomy, re-creating the native ACL footprints remains a challenge.